Effects of Urbanization on River morphometry: A case study for Nag River Urban Watershed using Geomatics Approach - Ranade, Pinak; Katpatal, Y.B. (Journal on Geoinformatics, Nepal, 2008)
Urbanization is responsible for the unexpected environmental degradation, which in turn has resulted in resource scarcity and damage to the towns and cities surroundings. Besides urbanization, the successive economic activities also exert tremendous pressure on the available limited natural resources. Especially in developing countries such as India, heavy urbanization has converted vast stretches of agricultural lands into built-up area, roads and other impervious surfaces, which obstructs water to get absorbed into the surface (UNEP 2000) It is estimated that 75% of pollution loads of all the rivers in India is due to urban wastewater. Nagpur is one of the fastest growing urban city with multitude of problems cropping up over the period of time. The severity of the problem can be understood by the fact that growing urbanization has changed the morphometry of Nag River. In this case study for Nag River urban watershed, remote sensing & GIS technologies are utilized to understand the impacts of growing urbanization on the river morphometry.